Study on effect of double austenitization treatment on fracture morphology tensile tested nuclear grade P92 steel. (February 2019) - Pandey, Chandan; Mahapatra, M.M.; Kumar, Pradeep; Kumar, Prakash; Saini, N.; Thakare, J.G.; Kumar, S.
Abstract: Effect of 'conventional normalizing and tempering' (CNT) and 'double austenitization based normalizing and tempering' (DNT) process on microstructure characteristic and mechanical behavior was studied forP92 steel. In CNT heat treatment, P92 steel is normalized at 1040 °C/air cool and tempered with 760 °C/2 h/air cool. In DNT heat treatment, initially normalizing was performed at 1040 °C for 1 h followed by water quenching. After that sample was normalized in the temperature range of 950–1150 °C for 1 h and tempered at 760 °C/2 h/air cool (950 °C-DNT1, 1050 °C-DNT2, 1150 °C-DNT3).Grain size for CNT and DNT1 treatment were measured 17 ± 7 μm and 12 ± 5 μm. A DNT treatment resulted in homogeneous microstructure formation that led to improved mechanical properties as compared to CNT treatment. The DN based heat treatment produced complete martensitic microstructure formation by complete dissolution of carbide precipitates. The optimized room temperature condition was obtained for the DNT 1 heat treatment. Highlights: The double austenitizing treatment (DNT) of P92 steel was performed for varying austenitizing temperature. Study the effect of DNT on grain refinement. Study the effect of DNT treatment on microstructure evolution and mechanical behaviour. Study on effect of DNT treatment on fracture surface morphology.